Faktor-Faktor Yang Berhubungan Dengan Kinerja Bidan Desa Sebagai Fasilitator Dalam Kegiatan Tabulin Dan Dasolin Di Kabupaten Sumenep - Fitriah Fitriah; Ani Margawati; Atik Mawarni (Jurnal Manajemen Kesehatan Indonesia, 2016)
One of the efforts to decrease maternal mortality rate (MMR) was an implementation of a delivery planning and complication prevention program (P4K) in activities of delivery mother’s saving and social fund for delivery conducted by village midwives. The aim of this study was to analyse factors relating to performance of a village midwife as a facilitator in the activities of delivery mother’s saving and social fund for delivery on the P4K in District of Sumenep in 2014.This was an analytic-observational study using a cross-sectional approach. Independent variables consisted of age, marital status, education, knowledge, experience, motivation, and supervision and a dependent variable was performance of village midwives. Number of samples were 90 village midwives working at 30 health centres. Data collection used a structured questionnaire that had been performed tests of validity and reliability. Furthermore, data were analysed using methods of bivariate (Chi-Square test) and multivariate (Logistic Regression test). The results of this research showed that respondents had low performance (30%), young age (31.1%), not married (24.4%), low education (42.2%), low knowledge (35.6%), low experience (77.8%), low motivation (26.7%), and low supervision (24.4%) in managing the activities of delivery mother’s saving and social fund for delivery at their work areas. Variables of knowledge (p=0.019) and supervision (p=0.037) statistically significantly related to the performance of village midwives. These two variables jointly influenced the performance of village midwives with p values= 0.07 and 0.013 respectively. District Health Office, Health Centre, and Indonesian Midwives Association need to conduct training, workshop, or socialisation to village midwives regarding the P4K particularly the activities of delivery mother’s saving and social fund for delivery.